Kolaborasi dan Kendali Ego: Meninjau Ulang Makna Kecerdasan di Era Digital - Setyaningrum, Rahmita; Asbari, Masduki; Amelia, Siska (Journal of Information Systems and Management (JISMA), 2025)
The digital era demands a redefinition of the concept of intelligence, which has tended to focus solely on the intellectual aspect. In reality, individual success in various fields is more often determined by the ability to collaborate, manage ego, and adapt socially. Through an analysis of Dr. Tirta's interview in the Endgame podcast, this paper explores the role of ego in inhibiting the collaboration process and the importance of social intelligence in building leadership that is relevant to the challenges of the times. A qualitative approach was used to examine the content of the discussion, which was then linked to various academic literature on leadership, collaboration, and social behavior. The results of the study indicate that cross-sector collaboration and control over personal ego are the main manifestations for creating effective collective solutions. This paper recommends the need for an emphasis on character education and collaboration as part of developing intelligence in the digital era.